Studi Penerapan ANN (Artificial Neural Network) Untuk Menghilangkan Harmonisa Pada Gedung Pusat Komputer - Edo Satrio Noviando; Edy Ervianto; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In electrical systems, power quality is something that must be considered, the power quality assessment can be viewed from various aspects, such as the continuity in the supply of electric energy, stable frequency and voltage on the transmission of electrical energy, and power factor. Non-linear load is a contributor of harmonics that can interfere with the quality of electrical power so used filters for the prevention of electrical harmonics. As science, it is increasingly developing technologies to minimize electrical harmonics, one of which is the Artificial Neural Network. This research will discuss the characteristics of the artificial neural network is used to solve the problem of harmonics on PUSKOM building .Keyword: Harmonics, Artificial Neural Network, Non Linier Load